Historical development of money: From trade to tokens - Petrović, Danijela; Damjanović, Gordana (Zbornik radova Filozofskog fakulteta (1990), 2023)
The timeless relevance of money points to the need, in addition to its economic functions and importance, to refer to its social and institutional aspects. The fact that it is one of the few categories that has survived during the development of civilization, has influenced money to be the subject of interest not only for economists, but also for historians, philosophers, lawyers, and computer scientists. The origin of money is linked to primitive forms of social life, so that the issue of money in modern conditions of life and work would gain a new context. The concept of money and its evolution are inextricably linked to technological progress, although the same, considering that it is not constrained by legal or cultural restrictions, is incomparably faster. In addition to cryptocurrencies, which today are increasingly created by teams of experts in the field of economics, marketing, programming, supported by large investment funds, tokens are experiencing increasing popularity, especially irreplaceable ones. The irreplaceability of tokens comes from their uniqueness, which is confirmed by the record on the blockchain. Their application is possible for any form of computer-generated file. Seen as a digital 'watermark,' a token can establish the authenticity of a digital file-image, video clip, audio file, or cryptocurrency. The ways in which tokens, through the transactions in which they are used, redefine the relationship between value and objects in the market, have found their application in many areas where authorship is valued. The question is whether their enormous popularity is based on real value. The aim of the research in the paper is to point out the importance of money as a historical and sociological category. In addition to the presentation of the historical development of money, the analysis in the paper seeks an answer to the question of whether cryptocurrencies can play the role of money that existed in forms before their appearance. In the analysis of the origin, history and development of money, a historical and content analysis method was used, which includes the analysis of relevant regulations in the field of money functioning, regardless of its form. The comparative-historical approach to money and the relationships created by the establishment of the commodity-money economy are significant for the analysis of money from a sociological point of view. An important socioeconomic issue when it comes to money is the question of the power it provides, the control of its creation and the struggle that takes place in that field among the state, banks, and debtors (Radonjić, 2010, pp. 45-66).